Perbedaan Prestasi Belajar Antara Siswa Tonsilitis Kronis Dengan Siswa Tidak Tonsilitis Kronis - RAHMAN, Fachroni (2015)
Background : Upper respiratory tract infection (URI) in Indonesia is a common cause of morbidity and mortality in children. Epidemiological data in seven province in Indonesia, prevalence of chronic tonsillitis 3,8% in the highest after acute nasopharyngitis which is a problem that is commonly found in children, given the high incidence and impact that can affect the quality of life of children, one of them is academic achievement. From the past studies there is a difference between farokah (2007) and khargoshae (2009) where farokah get a significant association in academic achievement suffering from chronic tonsillitis student below the average of the calss 76,6%, wheares non chronic tonsillitis by 23,4%. The research conducted by khargoshae only get a small sample size so it does not have a significant relationship between the size of the tonsils and academic achievement. Objective : To determine The Different Of Academic Achievment Between Student With Chronic Tonsillitis and Student Without Chronic Tonsillitis Methods : This study used cross sectional study. This study was conductd in January 2015 in SD Negeri 1 karangasem Surakarta with the sample of children in grade 1 to grade 6 as many as 230 children and devided in 2 groups, the cases are student with chronic tonsillitis and other groups are student without chronic tonsillitis as a control. Data were analyzed with chi-square Result : there were 70 student involved, consisting of 35 student with chronic tonsillitis and 35 student without chronic tonsillitis. From the result showed that the value of p= <0,001 for, where p<0,05. Conclusion : there is The Different Of Academic Achievment Between Student With Chronic Tonsillitis and Student Without Chronic Tonsillitis